Optimizing optimal path trace back for Smith-Waterman algorithm using structural modelling technique - Saliman, Nur Farah Ain (2012)
The optimizing of optimal path trace back system for Smith-Waterman algorithm using structural modelling techniques are presented in this paper. The objectives for this paper are to optimize the optimal path trace back scanning and to construct it using simple structural modelling architecture. Thus, this paper is highlighted on theoretical study and experimental design as a method of completion of proposed optimization techniques. Theoretical study emphasis on the mathematical and prove of concept of the proposed techniques. In experimental design, the proposed techniques code is developed, compiled and simulated using Altera Quartus II Version 9.0 EDA Tools targeted to Cyclone II EP2C35 at 50MHz clock oscillation. Both of the proposed technique is compared and analysed. The first design required more Logic Element (LE) as compare to second design which increased gradually in small interval. Therefore, the second design is the best approach in optimizing the optimal path trace back for Smith Waterman algorithm. In addition, the Design 2 is better than Design 1 since the runtime reduce up to 50%.